Screening with Nuclear and Other Techniques for Yield and N2 Fixation in Mungbean - Nantakorn Boonkerd; Precha Wadisirisuk; Achara Nantakit; Setha Siripin; Toshifumi Murakami (Agriculture and Natural Resources, 1993)
Mungbean (Vigna radiata) is a nitrogen fixing crop. To be most useful to farmers the recommended mungbean should obtain nitrogen from atmosphere through symbiotic fixation with rhizobia. The objective of this study was to select mungbean lines and rhizobial strains for high nitrogen fixation. Results obtained from screening of 423 mungbean lines indicated that there were variation in nitrogen fixation, nodulation nitrogenase activity and growth of mungbean lines. The mungbean lines VA 1948, VC 1776, VC 3128, VC 1830, VC 1693 and VC 2335 were higher in nitrogen fixation than the recommended cultivars. Using 15N natural abundance technique to quantify the amount of nitrogen fixed found that mungbean line fixed nitrogen ranging from 0-300 mg N per plant for 35 days. It was interesting to find that the hybrid line F7 of VC 2768 A/1560 D which was the highest fixing line could fix N up to 19.2 kg per rai, resulted in the farmer could get more profit of 235-300 baht when using this line. In estimating seasonal fixing of nitrogen, it was found that mungbean start fixing N in small amount at early stage and gradually increased until reach maximum at pod filling stage or about 41-45 days and the N fixed was gradually declined until stop fixing at maturity. Investigating of rhizobial strains infecting mungbean cultivars revealed that some strains were specific to a mungbean cultivar. However most mungbean rhizobia were effective. There were high correlation among nodule number, nodule mass, ARA and plant biomass. To quantify nitrogen fixation in mungbean under field condition it is necessary to find a suitable reference or non fixing crop. It was found that sorghum was the most suitable reference plant for measuring N2 fixation in mungbean. Under normal field condition the selected mungbean line could fix N upto 70%.